2020
DOI: 10.48550/arxiv.2012.02379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electromagnetic form factors of $Σ^{+}$ and $Σ^{-}$ in the vector meson dominance model

Zhong-Yi Li,
Ju-Jun Xie

Abstract: Based on the recently measurements of the e + e − → Σ + Σ− and e + e − → Σ − Σ+ processes by BESIII collaboration, the electromagnetic form factors of the hyperon Σ + and Σ − in the timelike region are investigated by using the vector meson dominance model, where the contributions from the ρ, ω, and φ mesons are taken into account. The model parameters are determined with the BESIII experimental data on the timelike effective form factors |G eff | of Σ + and Σ − baryons for center-of-mass energy from 2.3864 to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Previously, the VMD model have been widely used to study the EMFFs of the nucleon and the Λ hyperon, showing that it has the advantage to well describe the experimental data in the space-like and time-like region [15,27,[43][44][45][46]. Very recently, it has also been applied to investigate the EMFFs for Σ + and Σ − [25]. Encouraged by its success, we extend the model to study the EMFFs of the Λ c hyperon.…”
Section: Form Factors Of λ C Hyperon In the Vmd Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the VMD model have been widely used to study the EMFFs of the nucleon and the Λ hyperon, showing that it has the advantage to well describe the experimental data in the space-like and time-like region [15,27,[43][44][45][46]. Very recently, it has also been applied to investigate the EMFFs for Σ + and Σ − [25]. Encouraged by its success, we extend the model to study the EMFFs of the Λ c hyperon.…”
Section: Form Factors Of λ C Hyperon In the Vmd Modelmentioning
confidence: 99%
“…In the last two decades, the EMFFs of hyperons (i.e., Λ, Σ, Ξ) in the time-like region have also been investigated. Particularly, the enhancement of the cross sections in reactions e + e − → Y Ȳ near threshold were measured and analyzed [20][21][22][23][24][25]. It is found that the vector mesons and their resonances, as the intermediate states of the reaction, play important roles in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…The first theoretical estimates of the e + e − → B B cross sections and hyperon effective form factor, in the timelike region, were based on vector meson dominance (VMD) models [69,70]. More recently, with the emergence of accurate data for a variety of hyperons, new models have been proposed [6,[71][72][73][74], including improved VMD models [75][76][77][78][79][80]. Most of these studies focus on the Λ and Σ systems.…”
Section: Introductionmentioning
confidence: 99%